Faktor Yang Mempengaruhi Produktifitas Kerja Pada Badan Usaha Milik Desa - Muhammad Hengki Setiawan (SMARTINDO, 2022)
Purpose of this article: This study aims to determine the factors that affect work productivity in BUMDes, Panggung Lestari Village, Panggungharjo Village, Sewon District, Bantul Regency.Methodology: The method in this research is accidental sampling.Result: The results of this research can be used to measure the criteria, work fairness assessment, work productive motivation.